A review of offenders in a state psychiatric hospital - LIM, L. E. C. (Institutional Knowledge at Singapore Management University, 2000)
Patients remanded over a two-year period to Woodbridge Hospital by Court Order were studied retrospectively. Schizophrenia was the most common diagnosis, theft and robbery the most prevalent offences. Males greatly outnumbered females. There were important gender differences, with males tending to commit sexual offences and females, theft and mischief. Males were less likely to be acquainted with their victims but those who caused hurt were more likely to know their victims. Outrage of modesty and theft were more likely to be committed against strangers. The reconviction rate was 26%, with repeat offenders more likely to commit sexual offences and theft. Patients who had previous psychiatric hospitalisation were more likely to be attending follow-up prior to and after release from remand and were more likely to have schizophrenia. Those assessed to be fit to plead were either fined or given jail sentences. Unsoundness of mind and unﬁtness to plead were associated with further remand in this hospital.